Menyelisik Rahasia dan Hikmah Dibalik Variasi Bacaan Al-Qur’an - Assidiqi, Ahmad Zia’ulkhaq; Rosikh, Fahrur; Zunaih, Ahmad Iwan (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2024)
Recting Al-Qur’an is a form of worship that has great rewards, as said by the Prophet Muhammad saw. "One letter is equal to ten virtues." Apart from the Imam Hafs version of reading the Al-Qur'an which we have heard and studied since childhood, it turns out that in reading the Al-Qur'an there are many other variations of reading which are also equally correct. Amazingly, these reading variations not only enrich the style of reading the Al-Qur'an, but are also full of secrets & wisdom in them. This research was created with the aim of uncovering these secrets & wisdom. With this, hopefully we can broaden our insight and grow our love for the Al-Qur'an. The method the author uses is the library research method, where the author tries to collect the required information from several book sources, both classical and modern. As a result, the author found that there are at least eight secrets and wisdom in reading the Al-Qur'an, which are variously, presented along with examples, explanations and applications